Factors associated with victimization and perpetration of sexual aggression in Chilean university students - Hernández-Romero, Hebe (2023)
Introduction: Sexual aggression is a type of violence considered a public health problem that can affect people at any time of their lives. This investigation had three objectives: 1) to know the prevalence of victimization and perpetration of sexual aggression and its subtypes in the Chilean university context, 2) to identify the association of sex on the prevalence of victimization and perpetration of sexual aggression and its subtypes, and 3) to identify the association of alcohol consumption and victim-perpetrator relationship in the subtypes of victimization and perpetration of sexual aggression based on sex. Materials and methods: Descriptive cross-sectional study, with a sample of 1728 students (65.3% women) with a median age of 22 years. Results: 42.6% and 8.3% of the students reported at least one incident of victimization and perpetration of sexual aggression respectively in the last 12 months; an association of sex with the victimization of sexual aggression χ2 (1, N = 1728) = 101,425, p < .001 and its subtypes was identified; no sex association was identified with the perpetration of sexual aggression, but with sexual coercion χ2 (1, N = 1728) = 5,122, p < .05. In the case of alcohol consumption and victim-perpetrator relationship, they were associated with some subtypes of victimization and perpetration of sexual aggression. Conclusion: the findings contribute to the estimation of the magnitude of sexual aggression and associated factors in the university context, which should be explored in depth in order to create preventive programs for victimization and perpetration of sexual aggression.